Using Genotype Abundance to Improve Phylogenetic Inference. (20th February 2018) - DeWitt, William S; Mesin, Luka; Victora, Gabriel D; Minin, Vladimir N; Matsen, Frederick A
Abstract: Modern biological techniques enable very dense genetic sampling of unfolding evolutionary histories, and thus frequently sample some genotypes multiple times. This motivates strategies to incorporate genotype abundance information in phylogenetic inference. In this article, we synthesize a stochastic process model with standard sequence-based phylogenetic optimality, and show that tree estimation is substantially improved by doing so. Our method is validated with extensive simulations and an experimental single-cell lineage tracing study of germinal center B cell receptor affinity maturation.